Pengembangan Media Pembelajaran Flipbook Materi Seni Tari Kreasi Pada Mata Pelajaran SBDP Di Sekolah Dasar - Nuzla Rizkia Rahma,; Umar Umar,; Uus Kusnadi, (Jurnal Bintang Pendidikan Indonesia, 2023)
This research is motivated by the limited use of learning media used in the learning process, especially in the material of creative dance in learning the arts and crafts. The purpose of this study is to develop learning media flipbook creative dance art materials on SBdP subjects in elementary school. This study is a Design and Development Research, using research procedures proposed by Peffers, et al. (2007) namely identify the problems, desxribe the objectives, design & develop the artifact, test the artifact, evaluate the testing results, and communicate the testing results with data collection techniques using validation questionnaire sheets from experts and user response questionnaire sheets, namely teachers and learners. Development is done to evaluate the product on the feasibility of the media when used as a learning medium. Participants of this study involved material experts, media experts, and language experts for validation as well as teachers and students to provide responses in the use of media. The results of this study based on the validation of material experts get a percentage of 100% with the category “very decent”, assessment of media experts get a percentage of 91.88% with the category “very decent”, and linguists with a percentage of 93.75% with the category “very decent”. After testing the Learning media get an assessment of the teacher's assessment with a percentage of 100% in the category of “very good”and the assessment of students with a percentage of 95% in the category of “very good”. Based on these results, it can be concluded that the Learning media flipbook creative dance art material on SBdP subjects in elementary school is very feasible to serve as a learning media in Grade IV of elementary school.